Feasibility trial of Darwin OncoTreat and OncoTarget precision medicine testing to improve outcomes for patients with limited metastatic disease that failed first-line systemic therapy. - Rachel Radigan; Ashish Sangal; Dong Zhang; Jonathan Weber; Megha Schmalzle; Alexa Finkelstein; Vaibhav Duggal; Johnny Kao (PLoS ONE)
Despite significant progress in solid tumor oncology, including widespread genomic testing, metastatic cancer remains largely incurable and results in approximately 90% of cancer deaths. In the context of systems biology, RNA transcriptome-based (RNA-seq) testing is utilized to identify master regulator proteins that are putative drivers of tumor progression. After extensive preclinical testing and validation, Darwin OncoTarget and OncoTreat has been developed as a commercially available next generation precision oncology test with preliminary evidence of efficacy in treatment-refractory advanced cancers. We designed this pilot trial to assess the feasibility of integrating Darwin OncoTarget and OncoTreat testing in patients with oligometastases receiving comprehensive involved site radiotherapy. Eligible patients are adults with solid tumor oligometastases with up to 10 discrete tumors amenable to radiation therapy following prior first-line systemic therapy. Tumor biopsy is required to allow for precision medicine testing to supplement standard clinical management. Formalin fixed paraffin embedded tissue with >50% tumor will be sent to the Laboratory of Personalized Genomic Medicine at Columbia University Medical Center for Darwin OncoTarget and OncoTreat testing. Patients will either continue standard of care systemic therapy or proceed with an alternative FDA approved treatment informed by Darwin testing. This trial evaluates the feasibility and utility of integrating novel precision oncology testing in a community hospital setting. This study will utilize precision oncology testing in the population of induced, recurrent or persistent oligometastases that currently have limited or largely ineffective systemic treatment options. This trial represents an early attempt at integrating next generation precision medicine testing and systems biology in the context of radiation therapy.